Resilience and Self-Efficacy as Predictors of Anxiety: The Mediating Role of Growth Mindset in Diabetes Mellitus Patients - Ilne Ai Purana Adel; Hanggara Budi Utomo; Ninik Setiyowati (Kuras Institute, 2026)
Patients with diabetes mellitus frequently experience anxiety that negatively affects their quality of life and treatment adherence. Psychological resources such as resilience and self-efficacy are known to play protective roles, yet the psychological mechanisms explaining their influence on anxiety remain not fully understood. This study examined the mediating role of growth mindset in the relationship between resilience, self-efficacy, and anxiety among patients with diabetes mellitus. A cross-sectional correlational quantitative design using Structural Equation Modeling involved 160 patients with diabetes mellitus at hospitals in Kediri, selected through cluster sampling. Instruments included the resilience scale, self-efficacy scale, Growth Mindset Scale, and anxiety scale. Data analysis was conducted using SmartPLS 4.0. Resilience showed a significant negative effect on anxiety, while self-efficacy demonstrated a non-significant negative effect. Resilience and self-efficacy exhibited significant positive effects on growth mindset, and growth mindset demonstrated the strongest negative effect on anxiety. Growth mindset partially mediated the role of resilience on anxiety and fully mediated the role of self-efficacy on anxiety. Growth mindset functions as an active psychological mechanism in reducing anxiety related to disease burden. These findings provide an empirical basis for developing growth mindset-based psychoeducational interventions to strengthen self-efficacy and psychological resilience, thereby reducing anxiety, and improving treatment adherence among patients with diabetes mellitus.